Does accumulated physical load in different time windows affect hamstring injuries in elite football players? - Guitart-Trencha, M.; Sanchez-Sanchez, J.; Valle, X.; Garcia-Unanue, J.; Cos, F.; Alonso-Callejo, A.; Rodas, G.; Felipe, J. L. (Research in Sports Medicine, 2025)
Background This study aims to investigate how accumulated training load over different time windows (7, 14, and 28 days) influences the incidence of hamstring injuries in elite football players.